3D finite-difference migration of the field of refracted waves - A. Verpakhovskaya; V. Pilipenko; V.B. Budkevich (Геофизический журнал, 2015)
The method of 3D finite-difference migration of the field of refracted waves is proposed, which takes into account their penetration into refracting strata. Theoretical grounds and special features of the method of finite-difference deep migration of the field of refracted waves have been presented in the paper. Effectiveness and facilities of application of proposed method of 3D finite-difference migration of the field of refracted waves have been demonstrated on the model example.